Advances in the understanding of priapism - Hudnall, Matthew; Reed-Maldonado, Amanda B.; Lue, Tom F. (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Priapism, a persistent penile erection lasting longer than 4 hours and unrelated to sexual activity, is one of the most common emergencies treated by urologists. Priapism can be categorized as ischemic, recurrent ischemic (stuttering), and non-ischemic. Advances in understanding the pathophysiology of various types of priapism have led to targeted management strategies. This review aims to provide an up-to-date picture of the pathophysiology and management of priapism. A search of Medline and PubMed for relevant publications using the term “priapism” was performed. In addition to the “classical” articles, emphasis was placed on publications from January 2013 to September 2016 to evaluate the most recent literature available. Though advances in both basic and clinical research continue and effective treatment options are available, methods for the prevention of priapism continue to be elusive.